Effectiveness of probiotics on the growth and survival rate of catfish (Clarias sp.) in an aquaponics system - Afriansyah, Azmi; Yonarta, Danang; Shiddiq, Ja’far (Jurnal Mangifera Edu, 2025)
Applying probiotics to the recirculation system can support successful catfish production. This study aims to apply an aquaponic cultivation method that combines catfish (Clarias sp.) and water spinach cultivation by adding Probio-7 probiotics as a digestive aid to accelerate growth and improve the survival rate of catfish. This study was carried out at UPR Doa Mandeh, using the experimental design that compared the effects of probiotic application on aquaculture performance, and aimed to evaluate the effectiveness of weekly probiotics administration in a controlled aquaculture setting. Probiotics are introduced at the start of the maintenance period and reapplied weekly, following a 30% water loss, and promptly replaced with clean water. This routine was designed to maintain optimal water quality and microbial balance, supporting healthier aquatic life. The consistent probiotic treatment, aligned with systematic water management, highlights a practical approach to improving fish health and growth performance in sustainable aquaculture practices. The treatments used were without probiotics (P0) and the addition of probiotics at a rate of 0.25 mL L- 1 water (P1). The results of the research activities in P1 showed absolute length growth of 16.71 cm, absolute weight of 16.44 g, feed efficiency of 84.3%, and fish survival rate of 79%. These values were higher than those in P0, which had an absolute length growth of 5 cm, absolute weight of 11.94 g, feed efficiency of 84.3%, and fish survival rate of 77%. Water quality during the study remained within the optimal range, supporting the growth and survival of catfish.